(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1987)
The earliest, most classical carvings of the crescent and V-rod, the double disc with Z-rod, and the Pictish beast are found in three distinct, fairly localized areas and can be ascribed to slightly different dates. The sequence of decline into simplified forms offers a method of determining the relative ages of individual examples. F B